Minociclina e imunoterapia no tratamento da pitiose experimental em coelhos - Zimmermann, Carine Eloise Prestes (2020)
Pythiosis is a chronic disease caused by the oomycete Pythium insidiosum that affects both animals and humans. The main animals affected are the equines and canines, generating a worrying clinical picture. If not identified and treated rapidly, pythiosis can be fatal, so early diagnosis of the disease is still in its early stages, before it attacks vital organs. Treatment of pythiosis is difficult due to the fact that it does not respond well to drugs commonly used in fungal diseases, since the etiologic agent does not have ergosterol in its membrane. Thus, therapeutic alternatives have been investigated, among them immunotherapy and antibiotic drugs. In this context, the present study evaluated the in vivo effect of minocycline alone and in combination with immunotherapy in the treatment of experimental pythiosis in rabbits. Twenty five rabbits, aged three months old and subcutaneously inoculated with Pythium insidiosum zoospores were divided into four groups (n=5): treated with minocycline (10 mg/kg/day twice daily), treated with immunotherapy (34 mg subcutaneously every 14 days), treated with minocycline plus immunotherapy, untreated (control group, (n=5) and treated (control healthy, n=5). The treatments were started 30 days after inoculation and continued for 70 days. The subcutaneous nodular injury areas in infected groups were measured every seven days after the beginning of treatment. Only the rabbits that developed lesions were selected for this study. When compared with the control group over 70 days, the minocycline and minocycline plus immunotherapy groups of rabbits with pythiosis showed significantly reduced injuries. The histopathology showed the presence of inflammation, macrophages and eosinophils. Grocott’s staining revealed irregular hyphae-like structures that were ramified and occasionally septate. The infected and untreated group differed significantly increased in relation to the healthy group only in the hydrolysis of ADP and AMP. The results both showed that E-NTPDase and E-5'-nucleotidase activities were decreased in the immunotherapy-treated groups, which consequently increased the extracellular concentration of extracelular ATP, ADP and AMP. E-ADA activity did not change in the context of infection with the oomycete. Our results suggest that minocycline has fungistatic activity and that the combination of minocycline and immunotherapy is more effective than the individual therapies tested. And, the results reiterate the hypothesis of purinergic system receptor involvement in the modulation of immune response also for platelets, and that the nucleotides and adenine nucleoside interact for modulation of the Th1 response to occur.